1999
DOI: 10.1177/0310057x9902700505
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Controlled Analgesia in Postoperative Cardiac Surgery

Abstract: The purpose of this study was to assess, in the early postoperative period of cardiac surgery, the efficacy of patientcontrolled analgesia (PCA) versus nurse-administered intravenous morphine followed by oral acetaminophen with or without codeine. Patients undergoing coronary bypass and/or valvular surgery were recruited. All were under 75 years of age and were in stable angina with no ischaemic attacks within the last three months. Visual analog scores (VAS) were used for pain assessment. Pulmonary function t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…[1][2][3][4] Although the use of patient-controlled analgesia (PCA) is well established for major abdominal and orthopedic surgeries, [3][4][5][6] little has been published about its use after cardiac surgery. [7][8][9][10][11][12][13] Conventional bolus PCA may be less effective because of disorientation in the intensive care unit (ICU) environment, and poor retention of preoperative learning. 11 The addition of a background morphine infusion to morphine PCA may improve patient analgesia and comfort.…”
Section: Conclusion : L'aac Avec La Morphine Réduit Efficacement La Dmentioning
confidence: 99%
“…[1][2][3][4] Although the use of patient-controlled analgesia (PCA) is well established for major abdominal and orthopedic surgeries, [3][4][5][6] little has been published about its use after cardiac surgery. [7][8][9][10][11][12][13] Conventional bolus PCA may be less effective because of disorientation in the intensive care unit (ICU) environment, and poor retention of preoperative learning. 11 The addition of a background morphine infusion to morphine PCA may improve patient analgesia and comfort.…”
Section: Conclusion : L'aac Avec La Morphine Réduit Efficacement La Dmentioning
confidence: 99%
“…Patients in the phase 1 group, who discontinued the PCA system at 40 h, showed considerably higher VAS scores at POD 3-5 and frequently required additional analgesic drugs, including oral NSAIDs or intravenous pentazocine. Although previous investigations of intravenous PCA discontinued the PCA at POD 2-3 [12][13][14][15][16], we consider that employing PCA for only 2-3 days after cardiac surgery is not sufficient. Similarly, when thoracic epidural analgesia (TEA) was discontinued at POD 3, it did not shorten the length of hospital stay or rehabilitation procedure [17].…”
Section: Discussionmentioning
confidence: 78%
“…However, several studies have reported no significant difference in terms of analgesic efficacy [7,8,48,50,52]. It should be noted that in these latter studies, the authors paid particular attention to care by conventional analgesia.…”
Section: Pca Versus Conventional Opioid Analgesiamentioning
confidence: 99%
“…Walder et al in a recent meta-analysis which included 2, 111 patients [5], analyzed the studies comparing PCA with conventional opioid analgesia nurse administered by intramuscular [7,8,46,47], subcutaneous [48] or intravenous [49,50] routes or by continuous perfusion [51,52].…”
Section: Pca Versus Conventional Opioid Analgesiamentioning
confidence: 99%
See 1 more Smart Citation